International cooperation in bankruptcy and insolvency matters. - Bob Wessels; Hon. Bruce A. Markell; Jason Kilborn (Oxford University Press, 2009)
International Cooperation in Bankruptcy and Insolvency Matters is published in cooperation with the International Insolvency Institute and the American College of Bankruptcy. The Honorable Bruce A. Markell, Dr. Bob Wessels and Prof. Jason Kilborn provide readers with invaluable insights into the origins, development, and future of communication and cooperation in cross-border insolvency cases between practitioners and the courts.